Global characteristics and trends in research on Candida auris - Wang, Qihui; Cheng, Shitong; Wang, Yinling; Li, Fushun; Chen, Jingjing; Du, Wei; Kang, Hui; Wang, Zhongqing (Frontiers in Microbiology, 2023)
Introduction Candida auris, a fungal pathogen first reported in 2009, has shown strong resistance to azole antifungal drugs and has caused severe nosocomial outbreaks. It can also form biofilms, which can colonize patients’ skin and transmit to others. Despite numerous reports of C. auris isolation in various countries, many studies have reported contradictory results. Method A bibliometric analysis was conducted using VOSviewer to summarize research trends and provide guidance for future research on controlling C. auris infection. The analysis revealed that the United States and the US CDC were the most influential countries and research institutions, respectively. For the researchers, Jacques F. Meis published the highest amount of related articles, and Anastasia P. Litvintseva’s articles with the highest average citation rate. The most cited publications focused on clade classification, accurate identification technologies, nosocomial outbreaks, drug resistance, and biofilm formation. Keyword co-occurrence analysis revealed that the top five highest frequencies were for ‘drug resistance,’ ‘antifungal susceptibility test,’ ‘infection,’ ‘Candida auris,’ and ‘identification.’ The high-frequency keywords clustered into four groups: rapid and precise identification, drug resistance research, pathogenicity, and nosocomial transmission epidemiology studies. These clusters represent different study fields and current research hotspots of C. auris. Conclusion The bibliometric analysis identified the most influential country, research institution, and researcher, indicating current research trends and hotspots for controlling C. auris.